Eco-Friendly Treatment of Clarias spp. Fish Farm Wastewater via Phytoremediation with Ipomoea Aquatica and Lemna Minor - Nur An-nisa Putry Mangarengi; Andi Fitriani Afrianti Kasim; Muhammad Anshari Caronge; Muhammad Firdaus (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2026)
Aim: This study aims to assess the effectiveness of phytoremediation using Ipomoea aquatica and Lemna minor in reducing contaminants in catfish aquaculture wastewater, with particular attention to the effects of plant species and residence time in the wastewater. Methodology and Results: The phytoremediation tanks were constructed from Glass with dimensions of 40 cm (L) × 25 cm (W) × 30 cm (H). The effluent tank was made of a plastic basin with an approximate capacity of 3 liters. The treatment was conducted using a batch system. The independent variables in this study were plant type and retention time. The dependent variables comprised Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), phosphate and ammonia concentrations in the wastewater. The effectiveness of contaminant reduction varied depending on plant type and retention time, with significant reductions observed. The combination of Ipomoea aquatica and Lemna minor, with a retention time of 10 days (T3D3), achieved the highest removal efficiencies for BOD (96.15%), COD (83.63%), and 95.9% for Ammonia and Phosphate (91.87%). Conclusion, significance, and impact study: The phytoremediation process using different plant types and retention times effectively reduced BOD, COD, TSS, Ammonia, and phosphate levels in catfish aquaculture wastewater. Notwithstanding these advancements, the application of a combination of Ipomoea aquatica and Lemna minor for phytoremediation to mitigate pollutants in catfish aquaculture wastewater remains relatively unexplored.